The Android Application “Haji Pintar” And Independent Pilgrimage - Malik, Hatta Abdul; Sulistio, Sulistio; Jarong, Koree (International Journal Ihya' 'Ulum al-Din, 2024)
This article aims to find out the usability of the "Haji Pintar" Android application, Directorate General of PHU, Ministry of Religion, for the independence of Semarang City Hajj Pilgrims and to find out the factors that influence the low use of the Haji Pintar" application among Semarang City Hajj pilgrims. To achieve the objectives of this article, an exploratory study was used. The survey results showed a positive response to the usefulness of the application for Hajj independence for those who have performed the Hajj pilgrimage. Meanwhile, the factor that influences the low use of Haji Pintar applications is that the majority of Hajj pilgrims are elderly who have difficulty using devices.